Diagnosis of OLTC via Duval Triangle Method and Dynamic Current Measurement - Ahmad Khiar, Mohd Shahril; Md Thayoob, Yasmin Hanum; Yang Ghazali, Young Zaidey; Ab Ghani, Sharin; Sutan Chairul, Imran (2013)
Power transformers studies have shown that the main cause of power transformers failures is the On Load Tap Changer (OLTC). OLTC failure occurs due to the insulation degradation and contacts failure inside it. Other than that, contacts wear influences the OLTC performance and this phenomenon has not been deeply investigated. The worn contacts will cause hotspots in the OLTC tank and cause the insulating oil to degrade faster. Consequently, this will lead to the damage of complete transformer unit. Thus, the research work that has been carried out applied three different stages related to the diagnosis of OLTC. Firstly, fault detection of power transformer's OLTC is done mainly based on the results of the DGA interpretation by using the latest Duval Triangle method. Then, the results that obtained from latest Duval Triangle method are compared with the results carried out from Dynamic Current Measurement (DCM). Finally, research validation through visual inspection is applied to validate the results obtained from both DGA and DCM.